Relapsing fetal bilateral hydrothorax, an isolated expression of a vein of Galen aneurysmal malformation. (27th January 2015) - Mannaerts, Dominique; Muys, Joke; Ramaekers, Paul; Jacquemyn, Yves
Abstract : We report a case of bilateral fetal hydrothorax presenting at 20 weeks of pregnancy, spontaneously resolving at 22 weeks and severely relapsing at 28 weeks in a fetus with normal karyotype. The cause was a high-output heart failure caused by vein of Galen malformation.